COMPRÉHENSION DAN EXPRESSION MODUS SUBJONCTIF DALAM TEKS: (STUDI KASUS PADA MAHASISWA SASTRA PERANCIS UNHAS ANGKATAN 2015) - LaluMutmainnah Mutmainnah; Muhammad Hasyim; Masdiana Masdiana (JISOS: JURNAL ILMU SOSIAL, 2022)
This thesis is entitled "The Understanding and expression of the subjunctive mode in a text: case study of students from the French department of UNHAS from the promotion of 2015. The research aims to identify the errors of students, in particular those of the class of 2015, using the subjunctive mode.The method used in this research is both qualitative and quantitative in the collection of data. The latter is conducted by distributing questionnaires and questions related to the subjunctive mode. The test is designed in the form of comprehension and expression. Then, the marks obtained by the students are classified according to the number of errors. The ranking follows the defined criterion from 0 to 5 (from very weak to strongest). The result of this research shows that 54% of students have the ability to recognize and conjugate the subjunctive mode. Moreover, 55% of them do not yet have the ability to apply this mode in the form of a written text